The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.3390/ijerph20021584
|View full text |Cite
|
Sign up to set email alerts
|

Rheumatoid Arthritis Associated with Dry Eye Disease and Corneal Surface Damage: A Nationwide Matched Cohort Study

Abstract: Rheumatoid arthritis is potentially connected to ocular disorders, such as corneal inflammation and lacrimal gland destruction. This study aimed to evaluate the risk of dry eye disease (DED) and corneal surface damage among patients with rheumatoid arthritis. In a nationwide cohort study, we utilized Taiwan’s National Health Insurance research database and conducted propensity score matching to compare the risks of DED and corneal surface damage between patients with and without rheumatoid arthritis. Proportio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…Some studies on Sjogren syndrome and Rheumatoid arthritis reported the prevalence of dry eye about 23 per 1000 person-years. 10,11 MS disease pathogenesis has integral parts of the inflammatory cytokines secreted by Th1 and Th17, resulting in increased blood-brain barrier permeability to monocytes and macrophages. Th1 cells are found in damaged parts of the CNS and are actively present in MS patients' bloodstream, which produces inflammatory cytokines.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies on Sjogren syndrome and Rheumatoid arthritis reported the prevalence of dry eye about 23 per 1000 person-years. 10,11 MS disease pathogenesis has integral parts of the inflammatory cytokines secreted by Th1 and Th17, resulting in increased blood-brain barrier permeability to monocytes and macrophages. Th1 cells are found in damaged parts of the CNS and are actively present in MS patients' bloodstream, which produces inflammatory cytokines.…”
Section: Discussionmentioning
confidence: 99%
“…This study investigated one of the extra-articular manifestations of RA potentially involving the eyes. Common ocular presentations of RA include corneal inflammation, lacrimal gland dysfunction, and uveitis, sharing similar pathogenic mechanisms to DED [ 28 , 29 ]. It was used in diagnosis and evaluating DED severity and its correlation with RA disease activity and duration, which was found to be a valuable tool as used previously in different diseases [ 30 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…The NHI research database contains comprehensive claims data of the insured beneficiaries, including demographic characteristics (e.g., date of birth and sex), medical diagnoses, prescription drugs, and medical expenditures. The NHI research database has been widely used for public health statistics and risk assessment [19][20][21].…”
Section: Data Sourcementioning
confidence: 99%